2006
DOI: 10.1021/ma0512760
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Photochromic Polymer Brushes by Atom Transfer Radical Polymerization

Abstract: This work reports on the grafting of methyl methacrylate polymer brushes containing spirobenzopyran pendant groups from flat silica surfaces and colloidal particles utilizing atom transfer radical polymerization (ATRP). The reaction conditions were optimized with respect to the kind of surface bound initiator, the type of halide and ligand used in the catalytic complex, the presence/absence of untethered initiator, and solvent type. This enabled synthesis of coatings up to 80 ± 3 nm thick with controlled spiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 60 publications
0
58
0
2
Order By: Relevance
“…Since their discovery, photochromic SPs have been incorporated into various materials, i.e., surface bound monolayers,7, 11–13 Langmuir monolayers,14 Langmuir‐Blodgett films,14 polymeric brushes,9, 15–17 photocontrollable surfactants,18 liquid crystalline materials,19 polymeric matrices,8, 15, 16, 20–36 organic/inorganic hybrid systems,37 colloidal particles,17, 38 ionic liquids (ILs)39–43 and initiators for radical polymerisations 44…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, photochromic SPs have been incorporated into various materials, i.e., surface bound monolayers,7, 11–13 Langmuir monolayers,14 Langmuir‐Blodgett films,14 polymeric brushes,9, 15–17 photocontrollable surfactants,18 liquid crystalline materials,19 polymeric matrices,8, 15, 16, 20–36 organic/inorganic hybrid systems,37 colloidal particles,17, 38 ionic liquids (ILs)39–43 and initiators for radical polymerisations 44…”
Section: Introductionmentioning
confidence: 99%
“…An effective approach to overcome these barriers is to functionalize the silica surface with polymers that are identical or structurally similar to the matrix polymers. Among the widely pursued functionalization strategies is the 'grafting from' method [8,9], in which monomers or initiators are first attached to the silica surface to serve as starting points for propagation. For example, the silicabound azo moieties have been used in the conventional radical polymerization to graft vinyl polymers onto silica surfaces [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…43 [76,77] The polymers were grown from initiatorfunctionalized silica nanoparticles by atom-transfer radical polymerization. It was found that, in contrast to analogous polymer solutions, the particulate dispersion viscosity increased on exposure to UV light due to particle aggregation.…”
Section: Silica Nanoparticlesmentioning
confidence: 99%